Echinacoside ameliorates the memory impairment and cholinergic deficit induced by amyloid beta peptides via the inhibition of amyloid deposition and toxicology. Issue 6 (5th June 2017) - Shiao, Young-Ji; Su, Muh-Hwan; Lin, Hang-Ching; Wu, Chi-Rei
Abstract : This study investigates the role of the amyloid cascade and central neuronal function on the protective effects of echinacoside in amyloid β peptide 1-42 (Aβ 1-42)-treated SH-SY5Y cells and an Aβ 1-42-infused rat. Abstract : Echinacoside is a phenylethanoid glycoside and possesses neuroprotective activity in vitro and in vivo . This study investigates the role of the amyloid cascade and central neuronal function on the protective effects of echinacoside in amyloid β peptide 1-42 (Aβ 1-42)-treated SH-SY5Y cells and an Aβ 1-42-infused rat. Echinacoside inhibited Aβ 1-42 oligomerization in vitro and restored the cell viability that was reduced by Aβ 1-42 in SH-SY5Y cells. Intracisternal infusion with Aβ 1-42 by an osmotic pump caused cognitive deficits, an increase in amyloid deposition and acetylcholinesterase activities, and a decrease in the brain's levels of acetylcholine and dopamine. Echinacoside reduced the cognitive deficits and amyloid deposition, and it reversed the cortical cholinergic dysfunction that was caused by Aβ 1-42 in rats. Echinacoside further reversed the memory impairment in the Morris water maze task caused by scopolamine in mice. Therefore, we suggest that echinacoside ameliorated cognitive dysfunction that was caused by Aβ 1-42 by blocking amyloid deposition via inhibiting amyloid oligomerization and reversing the cortical cholinergic neuronal function via decreasing amyloid neurotoxicity.